Quantitative Structure Activity Relationship (QSAR) - Abhilash M (International Journal of Pharma and Bio Sciences, 2010)
Quantitative structure—activity relationship (QSAR) represents an attempt to correlate structural descriptors of compounds with activities. The physicochemical descriptors include numerical parameters to account for physical and electronic properties, steric effect, topology fragment compositions, hydrophobicity of analogous compounds, as well as calculated properties of the three-dimensional (3D) structures of the compounds. The 3D properties include scalar parameters like solvent-accessible surface area or hydrophobic surface area. They also include field-type reductions of the structure that represent steric interactions, electrostatic potentials, hydrogen-bonding potential, hydrophobic interactions, and so on.